PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA MANAJERIAL (Studi pada Hotel di Kota Yogyakarta) - Rahayu, Eka Ningsih Puji (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2018)
This study aims to determine the effect of budgetary participation on managerial performance with decentralization, leadership style, and motivation as moderating variables. Primary data from 36 respondents consisting of hotel manager, heads of divisions and employees were obtained through direct survey from one hotel in Yogyakarta. Regression analysis were run four times to test four hypotheses. The results shows that only decentralization variable was found as moderating variable in strengthening the effect of budgetary participation on managerial performance.